2021
DOI: 10.1186/s12889-021-10471-y
|View full text |Cite
|
Sign up to set email alerts
|

PM2.5 exposure and anxiety in China: evidence from the prefectures

Abstract: Background Anxiety disorders are among the most common mental health concerns today. While numerous factors are known to affect anxiety disorders, the ways in which environmental factors aggravate or mitigate anxiety are not fully understood. Methods Baidu is the most widely used search engine in China, and a large amount of data on internet behavior indicates that anxiety is a growing concern. We reviewed the annual Baidu Indices of anxiety-relate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…The use of the Baidu index accounts for shortcomings in the social media data used in this study. More importantly, the Baidu index is being increasingly used to analyze the relationship between the attributes of urban reality and PHS across a wide area by providing geographic data tags (Zhao et al, 2020b(Zhao et al, , 2021Chen et al, 2021a). At the national scale (i.e., China), Wang and Loo (2019) used the Baidu index and found notable hierarchical differences in the number of Internet news reports obtained by cities.…”
Section: Introductionmentioning
confidence: 99%
“…The use of the Baidu index accounts for shortcomings in the social media data used in this study. More importantly, the Baidu index is being increasingly used to analyze the relationship between the attributes of urban reality and PHS across a wide area by providing geographic data tags (Zhao et al, 2020b(Zhao et al, , 2021Chen et al, 2021a). At the national scale (i.e., China), Wang and Loo (2019) used the Baidu index and found notable hierarchical differences in the number of Internet news reports obtained by cities.…”
Section: Introductionmentioning
confidence: 99%
“…Recently it was therefore of note that case-crossover and a timeseries studies identified short-term higher SO2 exposure associated with more frequent presentation to health services with anxiety symptoms [21,25]. Few other studies have recently been added to the evidence base [50].…”
Section: Epidemiological Associations Between Air Pollutants and Ment...mentioning
confidence: 99%
“…Environmental factors, including air pollution, are risk factors for mental health conditions. Several studies have shown that airborne pollutants, including volatile organic pollutants and particulate matter, are associated with depression and anxiety [13][14][15]. Ventilation, which involves supplying air into indoor environments through mechanical or natural forces (i.e., air conditioning and windows, respectively), can reduce the concentration of indoor air pollution, such as volatile organic compounds, formaldehyde, and radon [16,17], improve indoor air quality, and is beneficial to cognitive function and respiratory health for older adults [17,18].…”
Section: Introductionmentioning
confidence: 99%